1997
DOI: 10.17763/haer.67.2.p1066147824v8l8t
|View full text |Cite
|
Sign up to set email alerts
|

Dancing with Bigotry: The Poisoning of Racial and Ethnic Identities

Abstract: By analyzing issues and messages in the mass media and recent news events, Lilia Bartolomé and Donaldo Macedo further the political discussion that problematizes the current discourse in education around ethnicity and race. The authors' discussion moves us beyond the monolithic constructs of Whiteness and "otherness" to recognize the complex interpenetrations and dynamics of ethnic and racial relations in the United States. In this article, the authors reveal how the politics of racism and division do not belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(22 citation statements)
references
References 4 publications
0
21
0
1
Order By: Relevance
“…Our challenge then is how to guide teacher candidates to continue to question practice and not be absorbed into school cultures that systematically violate immigrant children's dignity and contribute to their educational failures. Bartolomé and Macedo (1997) argue that "the politics of racism and division do not belong solely to extremist hate groups, but are an unacknowledged and potent part of mainstream American ideology, thought, and action" (p. 222). In this article, we have shown that practices of symbolic violence and coded language-that is, covert institutionalized racism-are abundant both in public schools and in universities where teachers are prepared.…”
Section: Discussionmentioning
confidence: 99%
“…Our challenge then is how to guide teacher candidates to continue to question practice and not be absorbed into school cultures that systematically violate immigrant children's dignity and contribute to their educational failures. Bartolomé and Macedo (1997) argue that "the politics of racism and division do not belong solely to extremist hate groups, but are an unacknowledged and potent part of mainstream American ideology, thought, and action" (p. 222). In this article, we have shown that practices of symbolic violence and coded language-that is, covert institutionalized racism-are abundant both in public schools and in universities where teachers are prepared.…”
Section: Discussionmentioning
confidence: 99%
“…Like many U.S. schools, Valley Middle School hopes that the Latino/a students can be served by being assimilated into the greater culture (Gandara & Contreras, 2009;Garcia, 2009). This strategy for serving these students does not work and often alienates students from the school and the education they want and need (Bartolome, 1997;Delpit, 1992;Trueba, Bartolome, & Macedo, 2000). The Latino/a students, coming from a different culture and experience, struggle to find their place in this European American school and ways to relate to the non-Latino/a students in the school.…”
Section: School Affordances: Support and Safetymentioning
confidence: 99%
“…By offering these academic works, the attempt was to begin to fill in the missing theories necessary to form a complete history of humanity. Works by scholars such as Swidler (1986) and Bartolome and Macedo (1997) attempted to explore the symbolism and cultural constructs that are used within Native American cultures as a way to eliminate the racial discrimination in society and education. While the above works were recognized among Native American scholars, little attention has otherwise been paid to the plethora of information available regarding Indigenous epistemology, science, technology, and general philosophy.…”
Section: Multiculturalism and Manifest Destinymentioning
confidence: 99%